Factors associated with utilization of skilled service delivery among women in rural Northern Ghana: a cross sectional study - Gudu, William (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Ghana’s current Maternal Mortality Ratio (MMR) of 319 per 100,000 live births makes achievement of the Sustainable Development Goal of 70 maternal deaths per 100,000 live births or less by 2030 appear to be illusory. Skilled assistance during childbirth is a critical strategy to reducing maternal mortality, yet the proportion of deliveries taking place within health facilities where such assistance is provided is very low in Ghana, with huge disparity between urban and rural women. To address the gap in skilled attendance in rural Upper East Region, the Ghana Health Service (GHS) in 2005 piloted a program that involved training of Community Health Officers (CHOs) as midwives. This study explored factors associated with skilled delivery services utilization in a predominantly rural district in Ghana. METHODS: A cross-sectional study, data was collected from a sample of 400 women between the ages of 15 and 49 years who had given birth a year prior to the study. We used frequencies and percentages for descriptive analysis and chi-square (χ (2)) test for relationship between independents factors and utilization of skilled delivery services. RESULTS: Of the 400 women included in the analysis, 93.3% of them delivered in a health facility. Almost all of the mothers (97.3%) attended or received antenatal care at their last pregnancy with 75.0% of them having four or more ANC visits. The proportion of women who received ANC and utilized skilled delivery services was high (91.5%). Mother’s educational attainment, ANC attendance, frequency of ANC visits, satisfaction with ANC services and possession of valid NHIS card significantly associated with utilisation of skilled delivery services. CONCLUSION: For a predominantly rural district, the percentage of women who deliver within health facilities where skilled assistance is available is very encouraging and a significant stride towards reducing Ghana’s overall MMR. Having four or more ANC visits and improving on the quality of care provided has a great potential of improving uptake of skilled delivery services. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-017-1344-2) contains supplementary material, which is available to authorized users.